Short-term stress: effects on cortisol levels and carotenoid spots in Arctic char ( Salvelinus alpinus ) - Backström, Tobias; Johansson, Kajsa; Brännäs, Eva; Nilsson, Jan; Magnhagen, Carin (Canadian Journal of Zoology, 2016)
Earlier studies have shown that the carotenoid pigmentation in Arctic char (Salvelinus alpinus (L., 1758)) is connected to stress responsiveness. These studies also suggested that the pigmentation is dynamic and can change quickly. Therefore, we wanted to investigate the effect of a short-term stressor on the number of carotenoid spots before and after certain time intervals after the stressor. Individuals were exposed to a net-restraint stressor for 1 min and then assigned a recovery time of either 0, 1, 2, 8, or 24 h. Photographs were taken before the stressor and after the recovery time to count carotenoid spots and to look at the relative changes over time. Behaviour during the stressor and cortisol levels after the assigned recovery time were evaluated. We found that the change in spottiness, measured as the ratio of spots after and before the stressor, changed with recovery time on the right side but not on the left side. Furthermore, left-side spots were correlated with struggling activity. Thus, carotenoid pigmentation seems to be lateralized, with more static spots on the left side connected to stress responsiveness, whereas spots on the right side seem to be more dynamic.